Novel Adaptive Background Segmentation Algorithm for Multiple Object Tracking - Ramalakshmi Kanthimathi, V; Germanus Alex, M (International Journal of Engineering and Technology, 2018)
Multiple object tracking plays a vital role in many applications. The objective of this paper is to track multiple objects in all the scenes of the video sequence. In this paper, an algorithm is proposed to identify objects between scenes by dividing the scenes in the video sequence. Within each scene, objects are identified and tracked between scenes by segmenting the background adaptively. The proposed method is tested on four publicly available datasets. The experimental results substantially proved that the proposed method achieves better performance than other recent methods.Â